Evaluation of cashew nut processing waste (CPW) as a non-conventional feed ingredient in the diet of tilapia Oreochromis mossambicus - Divi Balagopinath (KUFOS, 2018)
Abstract- The use of alternative feeds aims to maintain productivity and reduce animal production costs. This objective of this study was to determine the evaluation of cashew nut processing waste as a non-conventional feed ingredient. Value of cashew nut processing waste (CPW), as well as replacement of soybean meal (SBM) by CPW in the diet of tilapia, Oreochromis mossambicus. The experimental design was completely randomized with five treatments and three replicates. A total number of 300 healthy Oreochromis mossambicus with an average weight of (20.53±0.05) were stocked in each cylindro conical tanks. Total five iso-nitrogenous (30% CP) iso-caloric (6% CL) was prepared with graded replacement of soybean meal. Treatment 1 is fed without (CPW) and treatment 2 to treatment 5 was fed with 10% to 40% replacement of soybean meal. Feed will be provided ad libitum three times daily at 10, 13, and 17 hrs and faecal matter were collected for digestibility studies in morning times. The water quality parameters like temperature, pH, DO, total alkalinity, ammonical nitrogen, nitrite nitrogen and nitrate nitrogen are monitored weekly basis and the growth response were monitored on 12 days basis. On the experimental trial the fish fed with 40% replacement of soybean meal with CPW showed significant (P < 0.05) in all parameters like weight gain (50.1± 2.2), specific growth rate (2.1 ± 0.07), the nutrient utilization factors like FCR (0.7 ± 0.3), PER (2.8 ± 0.25), LRE (41.7 ± 8.2). The whole body composition of treatment 5 fed with 40% replacement of soybean meal with CPW showed significantly different in low moisture content, better crude protein, and crude lipid percentage. The digestibility coefficient of dry matter, crude protein, crude lipid and NFE is also showed significant different compared to other four treatments. The blood parameters like haemoglobin does not showed any significant difference in all the treatments, but in treatment 5 with 40% CPW shown lower values of SGOT and SGPT. Higher values of total protein and alkaline phosphatase level in same treatment. The digestive enzymes like protease and amylase is also showed significant difference between the treatments. The histological changes in liver showed less number of hepatic cells in treatment 1 to treatment 3. In treatment 4 and treatment 5 showed more number of hepatic cells. . It is concluded from the study that soybean meal could be replaced up to 40% in the diet of tilapia without compromising growth, nutrient utilisation and health status.